Immunologic correlates of protection and potential role for adjuvants to improve influenza vaccines in older adults. (July 2013) - McElhaney, Janet E; Coler, Rhea N; Baldwin, Susan L
The decrease in influenza vaccine efficacy in the elderly is associated with a decline in the stimulation of cell-mediated and cytotoxic T-lymphocyte responses required for clinical protection against influenza, and may be particularly problematic when this population is administered split-virus vaccines that lack conserved viral proteins. Adjuvants, which act through innate immune mechanisms, are known to enhance both humoral and T-cell-mediated responses to influenza vaccines in this population. Adjuvant effects including enhanced antigen presentation, activation and maturation of dendritic cells and production of inflammatory cytokines can drive the desired cell-mediated immune responses. Toll-like receptor ligands comprise one class of adjuvants, which interact with external and internal receptors associated with dendritic cells and other APCs, leading to the regulation and production of important inflammatory cytokines. Potential advances in the production of more effective influenza vaccines for older people include the addition of adjuvants to standard split-virus vaccines and the use of alternate routes of vaccine delivery to augment the response to influenza infection. In this review, the authors discuss the impact of immune senescence on the response to influenza vaccination, the correlates of protection against influenza disease and the progress being made in the design of better influenza vaccines for the population aged 65 years and older.